2014
DOI: 10.1109/tit.2013.2293573
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Ergodic Capacity of a Class of Fading Two-User Two-Hop Networks

Abstract: We consider a fading AWGN 2-user 2-hop network where the channel coefficients are independent and identically distributed (i.i.d.) drawn from a continuous distribution and vary over time. For a broad class of channel distributions, we characterize the ergodic sum capacity to within a constant number of bits/sec/Hz, independent of signal-to-noise ratio. The achievability follows from the analysis of an interference neutralization scheme where the relays are partitioned into M pairs, and interference is neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…It was shown in [26], [27] that IA can also be attained on fixed (not time-varying) channel coefficients. A different strategy of IA was developed in [28], [29] called ergodic IA, which makes interference aligned in the finite SNR regime and, as a result, provides significant rate improvement compared with the conventional time-sharing strategy in the finite SNR regime [28], [30]. The DoF of K-user MIMO IC has been considered in [13], [31], [32].…”
Section: B Previous Workmentioning
confidence: 99%
“…It was shown in [26], [27] that IA can also be attained on fixed (not time-varying) channel coefficients. A different strategy of IA was developed in [28], [29] called ergodic IA, which makes interference aligned in the finite SNR regime and, as a result, provides significant rate improvement compared with the conventional time-sharing strategy in the finite SNR regime [28], [30]. The DoF of K-user MIMO IC has been considered in [13], [31], [32].…”
Section: B Previous Workmentioning
confidence: 99%
“…Proof: We refer to Appendix I-C for the proof. Therefore, combining (10), (11), (12) and the result in Lemma 4 provides…”
Section: A Converse Of Theoremmentioning
confidence: 82%
“…In addition, for the case in which all channel coefficients are constant, Motahari et al [23], [24] proposed a different type of IA scheme based on number-theoretic properties of rational and irrational numbers and showed that the optimal DoF of K 2 is also achievable. Later, alternative methods of aligning interference in the finite signal-to-noise regime has been also proposed in [22], [25]- [27]. The concept of IA has been successfully adapted to various network environments, e.g., see [13]- [19] and the references therein.…”
Section: A Previous Workmentioning
confidence: 99%